Science Corner in Primary Classrooms: From the State/UT— Puducherry - Fernandez, George (THE PRIMARY TEACHER, 2022)
The Science Corner Manual is an initiative which is prepared and distributed by the UT of Puducherry to improve the attainment of learning outcomes in the subject of environmental studies for primarylevel students and to develop attitudes towards the subject. This manual includes the guidelines for the installation of a Science Corner in the classroom, a list of experiments that can be conducted in the classroom (under adult supervision), a list of local shops where teachers or the school authority could buy the material needed to conduct the experiments, teacher’s role while conducting the experiments, safety measures to be taken while conducting the experiment, etc.